ANTI-TTG AMONG CHILDREN WITH CHRONIC FUNCTIONAL CONSTIPATION UNRESPONSIVE TO 6 WEEKS OF TREATMENT OF CONSTIPATION - SADJADEI,Nooshin (2017)
ABSTRACT BACKGROUND Celiac disease is a glutten induced enteropathy. Some authors recommended screening celiac in children with constipation. There are studies to evaluate celiac disease in children with constipation. But most of them included children regardless to treatment failure. OBJECTIVE The aim of this study was to evaluate frequency of elevated anti TTG in children with constipation after failure to improve during 6 week of appropriate treatment of constipation. METHODS In this cross sectional study, 550 children with prolonged constipation were included. Place of study was Pediatric Gastroenterology clinic of Abuzar children’s hospital. Prolonged constipation was defined as a constipation which failed to resolved after 6 weeks of appropriate treatment. Constipation was defined according to ROME III criteria. After parental agreement, 5 mL of blood was obtained. Serum anti TTG level was measure using ELISA method by Orientec kit. Anti TTG>10 was considered positive if IgA was normal. SPSS version 16.0 (Chicago, IL, USA) was used for data analysis. Chi square, t-test, and Mann Whitney test used for data analysis. RESULTS In this study 550 children (m=277, f=273) were included. Mean age of the cases was 6.8±2.9 year. Anti TTG antibody level was 5.8±2.8 unit/mL. Of these case, 42 (7.6%) had positive anti-TTG antibody. Celiac disease was confirmed in 40 cases after histopathology examination. CONCLUSION Anti-TTG was positive in 7.6% children with chronic constipation who failed to respond after 6 week of treatment. Another multicenter study with longer follow up period is recommended.